SCALABILITY OF E-COMMERCE IN THE COVID-19 ERA - Dinesh, Sahana; MuniRaju, Y. (International Journal of Research -GRANTHAALAYAH, 2021)
The COVID-19 pandemic has had major influence on the people all over the world. This has also influenced the consumers to shop online owing to their apprehensions regarding the safety. Therefore, this has opened up huge opportunities to online retailers and platforms to increase their sales and revenue and at the same time posed several challenges. E-commerce business is becoming scalable as more and more people are forced to buy online due to their apprehension to go to physical stores in the time of pandemic. This study is aimed at understanding the factors that are causing an increase in the e-commerce transactions and also attempts to know the consumer behaviour during the COVID- 19 pandemic. Through a survey of 195 respondents, the study found that frequency of online shopping has increased during the pandemic period. The study suggests that both online and offline retailers have to invest in smarter technologies and improve customer engagement.